Serological Evidence of Hepatitis B and E and Dengue Coinfection in Chadian Patients and Impact on Lipidemia Profile - Alexandre Kanga Djasrabe; Borris Rosnay Tietcheu Galani; Moussa Mahamat Ali; Fissou Henry Yandai; Bessimbaye Nadlaou; Mayann Habkreo; Nicolas Yanou Njintang (International Journal of Hepatology)
Objective. Viral hepatitis is an endemic disease in Chad. However, few studies have documented coinfection cases and their impact on cardiovascular risk. This study is aimed at analyzing hepatitis B, E and dengue coinfection in a Chadian cohort and gauge its effect on lipidemia. Patients and Methods. From February to May 2021, 179 subjects were recruited from the Department of Gastroenterology and Internal Medicine of the National Reference University Hospital of N’Djamena and tested for viral hepatitis markers, including HBsAg and IgM/IgG anti-HEV and dengue infection, using the NS1/IgM/IgG kit. Serum transaminases and biomarkers of lipid profiles were assayed by colorimetry, and atherogenic indexes (AI) and coronary risk (CRI) were calculated. Results. Of the 179 subjects surveyed, 21.22% (38/179) tested positive for hepatitis B, 20% (27/135) for hepatitis E, and 1.66% (2/120) for dengue. However, most of the patients were found to be asymptomatic. Hepatitis B/E coinfection was more frequent in the study population (5.02%; 9/179) than dengue/hepatitis E coinfection (0.83%; 1/120; IgM). The prevalence of anti-HEV IgG antibodies was higher (18.52%) than that of IgM (1.48%). Furthermore, IgG antibodies levels in HEV-monoinfected subjects (11.05±1.93 IU/mL, N=15) were significantly higher (p<0.05) than in coinfected patients (5.40±1.31 IU/mL, N=9). Subjects coinfected with HEV/HBV were associated with a significantly higher risk of lipodystrophy (coronary risk: 88.89% vs. 35.3%, relative risk RR=2.55; p=0.014), than HEV-monoinfected subjects, as evidenced by higher mean levels of triglycerides levels (219.88±14.67 mg/dL vs. 191.82±4.66  mg/dL, p<0.05), more reduced HDL-C levels (9.05±1.62 mg/dL vs. 18.93±2.35 mg/dL, p<0.05), increased mean CRI (13.81±2.39 vs. 6.89±1.93, p<0.01), and AI (1.46±0.10 vs. 1.05±0.05, p<0.01) values. However, they had normal transaminase values and a lower risk of developing a liver injury, although not significant (alanine aminotransferase: 0% vs. 29.4%, RR=1, p=0.128; aspartate aminotransferase: 0% vs. 5.88%, p=1) than this group. Conclusion. HBV/HEV coinfection is frequent in the Chadian cohort and associated with an important risk of dyslipidemia. Further research is required to elucidate the mechanism of action.